Microwave assisted adsorption based elution: a benign green process optimized by Box-Behnken modeling yields pure vasicine from Adhatoda vasica - Subramaniam Shankar; Sivasubramanian Aravind (Green Processing and Synthesis, 2016)
Development of economical and rapid high yielding industrial processes for isolation of commercially important plant molecules have been in current industrial vogue. Adhatodavasica, a functional dietary supplemental plant, is found to harbor vasicine, a commercially important and physiologically active alkaloid. Attempts were made to increase the yields of vasicine by a viable “green” process – microwave assisted adsorption based elution (MAABE) with silica gel. Microwave (300 W) assisted extraction was done with 6% HCl/water (solid loading – 10%), which in 4 h yielded vasicine (8.8 mg/g of leaves, 0.88%). A Box-Behnken designed response surface methodology (RSM) optimized the extraction parameters to 9.31% solid loading, 6.64% HCl/water and 4.1 h, respectively. Further, adsorption based elution using silica gel and desorption with 70% ethanol/water yielded pure vasicine (1.12%) (recovery=93%, purity=95%). The adsorption isotherms studied to understand the adsorption mechanism suggested that the process followed the Langmuir theory. MAABE required less time and labor, in addition to its relative safety and as a “green” alternative process, to give high yields of commercially important vasicine.